2018
DOI: 10.1186/s40780-018-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

Possible associations of personality traits representing harm avoidance and self-directedness with medication adherence in Japanese patients with type 2 diabetes

Abstract: BackgroundInsufficient medication adherence in diabetes patients, of which numbers continue to increase globally, remains a critical issue. Medication adherence is multifactorial and determined by interactions among factors including socioeconomic status, health care team and system, condition, therapy, and patient-specific factors. On the other hand, personality traits have been studied in adherence other than to medication. Using the instruments of Temperament and Character Inventory (TCI), Harm Avoidance (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
3
14
1
1
Order By: Relevance
“…In this profile, therefore, gambling could be a dysfunctional habit acquired and maintained over time as a mechanism to avoid problems and difficulties in emotion regulation. Thus, it could represent a group of patients more inclined to present poor response to treatment, as various studies have previously shown (3941). As such, they may require treatment programs that incorporate techniques to improve these aspects, favoring a better response to therapy (8).…”
Section: Discussionmentioning
confidence: 92%
“…In this profile, therefore, gambling could be a dysfunctional habit acquired and maintained over time as a mechanism to avoid problems and difficulties in emotion regulation. Thus, it could represent a group of patients more inclined to present poor response to treatment, as various studies have previously shown (3941). As such, they may require treatment programs that incorporate techniques to improve these aspects, favoring a better response to therapy (8).…”
Section: Discussionmentioning
confidence: 92%
“…As another predictor of medical adherence in T2DM patients, BMI, diabetes knowledge, and family history of diabetes were identified. Tominaga et al reported that older age was significantly associated with better medication adherence [39]. A high BMI (obesity) and a family history of diabetes are significantly and positively associated with the risk of T2DM progression [4042].…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies about medication adherence in diabetes treatment, depression and medical costs are found to be consistent factors in systematic review [5]. Also, age [6], self-e cacy [7], and personality traits [6] are potential factors to be associated with medication adherence. However, knowing underlining potential factors does not mean to solve nonadherence problems because multiple factors may exist in each individual patient and some of them are not modi able.…”
Section: Introductionmentioning
confidence: 93%